Penggunaan Media Sosial pada Siswa Sekolah Dasar Kelas Tinggi di Kecamatan Kepahiang - Septy Dwi Fadillah; Feri Noperman; Resnani (Universitas Bengkulu, 2022)
The purpose of this research for describe social media use on grade school students high in the District Kepahiang. Type of this research is quantitative survey. Population on this research is all primary schools in the District Kepahiang, totaling 22 public elementary schools. Sample on this research is 170 students from grade 4 to grade 6 in 2 public elemantry school in District Kepahiang. Technique data collection and research instruments this use questionnaire. On research this technique data analysis using formula percentage. Results research this show that social media use of 170 students there are 164 students who use social media, age social media users from 9 years – 112 years, the most social media used that is Whatsapp (93.90%), YouTube (87.19%), Facebook (73.17%), TikTok (68.29%), and Instagram (56.09%). Public elementary school 03 Kepahiang students and public elementary school 22 Kepahiang normal access social media with use mobile phones (91%-97%), laptops (2%-9%), and tabs (1%-7%), they also using social media in various the place like at home (93%-98%) and at school (1%-5%). Students access social media with destination work Duty school (30%-60%), looking for entertainment (45%-50%), and as for elementary school students use social media for transaction sell buy although only little (2%).